The Indigenization and Hybridization of Food Cultures in Singapore - Lim, Tai Wei.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Pivot, 2019)
This pivot considers the use of porcelain vessels within multi-dialect cultural spaces in the consumption of cooked food in Singapore. In a place of ubiquitous hawker centres and kopitiams (coffee shops), the potteries used to serve hawker foods have a strong presence in the culinary culture of Singaporeans. The book looks at the relationship between those utensils, the food/drinks that are served as well as the symbolic, historical, socio-cultural and socioeconomic implications of using different kinds of porcelain/pottery wares. It also examines the indigenization of foreign foods in Singapore, using two case studies of hipster food - Japanese and Korean. While authentic Japanese and Korean cuisines find resonance amongst the youths of East Asia, some of them have adapted hybrid local features in terms of sourcing for local ingredients due to costs and availability factors. The book considers how these foods are hybridized and indigenized to suit local tastes, fashion and trends, and offers a key read for East Asian specialists, anthropologists and sociologists interested in East Asian societies.
Part I -- 1. Introduction -- 2. Food Vessels: A Brief Historical Survey of Ceramics Use for Food Consumption in Singapore's Hawker Centres and Coffee Shops (kopitiams) -- 3. Diversity in Southeast Asian Serving Vessels -- 4. Late Modernity: Food-Serving Vessels Used in the Mid-Twentieth century -- Part II. - 5. Promoting Singapore-Japan Ties Through the Soft Cultural Power of Food Diplomacy: The Hybridization, Cross-Pollination and Indigenization of Contemporary Japanese Food Culture in Singapore -- 6. The Korean Wave in Singapore's Multi-cultural Food Scene: Indigenization, Localization, Hybridization and Cross-Pollination -- Part III -- 7. Conclusion.
Keywords: Ethnology; Ethnology -- Asia; Culture; Race; Emigration and immigration; Sociocultural Anthropology; Asian Culture; Race and Ethnicity Studies; Human Migration